AB0709 SERUM IL-12/23 AND IL-17 LEVELS IN PATIENTS WITH SPONDYLOARTHRITIS WERE NOT INFLUENCED BY TNF-BLOCKADE. (2nd June 2020) - Murakami, M.; Nishimoto, N.
Abstract : Background: Spondyloarthritis (SpA) refers to a heterogeneous group of disorders with clinical features that can include axial and peripheral arthritis, inflammatory bowel disease, uveitis, and psoriasis. Several cytokines including interleukin (IL)-12/23, IL-17 and tumor necrosis factor (TNF) are involved in pathogenesis of SpA. It is assumed that TNF is the upstream cytokine in the cytokine cascade (Schett, et al., 2013). Objectives: To investigate whether TNF inhibitors decrease serum IL-12/23 and IL-17 levels in patients with SpA. Methods: Serum were obtained from 23 SpA patients (AS, 10 patients; PsA, 13 patients) enrolled in this study, at baseline, 24 and 48 weeks of TNF inhibitor treatment. Serum IL-12/23 and IL17 levels were measured using LEGEND MAX Human IL-12/IL-23 (p40) ELISA Kit (BioLegend) and Human IL-17A ELISA kit (Invitrogen), respectively. IL-6 levels, the other downstream cytokine, was measured using Lumipulse G600II (FUJIREBIO) as a control. Results: Any significant reduction in IL-12/23 levels (143.9±143.6 pg/mL at baseline, 156.3±117.1 pg/mL at 24 weeks and 139.3±118.1 pg/mL at 48 weeks), as well as that in IL-17 levels (13.6±51.9 pg/mL at baseline, 12.3±41.4 pg/mL at 24 weeks and 11.6±39.2 pg/mL at 48 weeks) were not observed in 23 SpA patients. On the other hand, serum IL-6 levels were significantly decreased after treatment (4.0±4.2 pg/mL at baseline; 1.8±1.4 pg/mL, p=0.002, at 24 weeks; 1.6±1.9 pg/mL, p=0.0002 at 48 weeks. Pain-VAS was significantly reduced at 24 and 48 weeks compared with that at baseline. No significant differences in serum levels of analyzed cytokines were observed in the AS group compared with the PsA group at baseline (IL-12/23 levels: 110.8±70.0 vs.169.3±180.3 pg/mL, p=0.28 ; IL-17 levels: 26.8±78.6 vs. 3.4±7.6pg/mL, p=0.08 ). Conclusion: TNF inhibitors did not alter serum IL-12/23 and IL-17 levels but reduced IL-6 levels in patients with SpA. These results imply that IL-12/23 and IL-17 expression might be regulated by alternative pathways. References: [1]Schett, et al. Toward a cytokine-based disease taxonomy. Nat Med. 2013 Jul; 19 (7):822-4 Disclosure of Interests: Miho Murakami Grant/research support from: Chugai, Eisai, Consultant of: Chugai, Norihiro Nishimoto Grant/research support from: Chugai, Eisai, Consultant of: Chugai, Speakers bureau: Chugai, Eisai, AYUMI, Mitsubishi Tanabe, AbbVie, Novartis, Nippon Kayaku, TOWA, Astellas, Kyowa Kirin